2019
DOI: 10.1002/cssc.201802799
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Cocatalyst Loaded on Calcium Titanate Photocatalyst for Water Splitting in a Flow of Water Vapor

Abstract: In water splitting by using heterogeneous photocatalysts, the use of a suitable cocatalyst has been recognized as one of the key factors in enhancing the photocatalytic activity. Although platinum is a representative cocatalyst for many heterogeneous photocatalytic reactions, it has not been used for photocatalytic water splitting, owing to its high catalytic activity for the reverse reaction of water splitting. In the present study, platinum nanoparticles were loaded as a cocatalyst on a calcium titanate phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
(45 reference statements)
1
28
0
Order By: Relevance
“…But it seems that the best method is to use at least two photocatalysts in different forms such as cocatalyst, doping the catalyst, and use of heterojunction structure. Noble metals such as platinum, nickel, silver, gold, and ruthenium have been used as co‐catalysts with semiconductors such as TiO 2 , 7‐10 CaTiO 3 , 11 CdS, 12,13 and g‐CN 14 . In doping, an impurity, metal or non‐metal, enters the photocatalytic structure and changes its optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…But it seems that the best method is to use at least two photocatalysts in different forms such as cocatalyst, doping the catalyst, and use of heterojunction structure. Noble metals such as platinum, nickel, silver, gold, and ruthenium have been used as co‐catalysts with semiconductors such as TiO 2 , 7‐10 CaTiO 3 , 11 CdS, 12,13 and g‐CN 14 . In doping, an impurity, metal or non‐metal, enters the photocatalytic structure and changes its optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium titanate (CaTiO 3 ) would be a suitable photocatalytic material for the assessment of the possibility of this new reaction system (eq 7), since it has been reported as a photocatalyst for water splitting, 22,23 CO 2 reduction, 5,24 and so on. 25 In this study for the first time, we found that a CaTiO 3 (CTO) photocatalyst loaded with a silver−manganese oxide (Ag−MnO x ) dual cocatalyst enabled the simultaneous production of CO and H 2 O 2 from CO 2 and H 2 O without the application of any external bias and consumption of any compounds, which is referred to as a Ag−MnO x /CTO photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the alkaline‐earth metal perovskite oxides are of great scientific interest for inventive applications owing to their remarkable merits like high chemical and photostability, low cost, earth‐abundant constituents, non‐toxic nature, favorable conduction band (CB) (above −0.1 eV) and valence band (VB) (below +2.0 eV) potential, etc . As a prototype, calcium titanate (CaTiO 3 ) with orthorhombic crystal structure has attracted growing attention in the field of photocatalysis …”
Section: Introductionmentioning
confidence: 99%